(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
In the field of English as a Foreign Language (EFL), learners often face considerable challenges in developing both receptive and productive skills. These barriers not only hinder communicative competence but also affect academic achievement. To overcome such difficulties, learners employ a variety of strategies, among which visual techniques and technology-enhanced tools have recently attracted increasing attention. This study investigates language-skill barriers and strategy use among local EFL learners, with a particular focus on integrating visual techniques into the development of reading and writing as representative receptive and productive skills. A quantitative method was employed, involving 122 first-year English-major students from three regions of Uzbekistan, surveyed through an online questionnaire. Besides three demographic questions, the instrument contained 15 main items designed to: (a) identify language-skill barriers, (b) explore individual strategies used by learners, and (c) evaluate the potential role of visualization-based techniques in overcoming these difficulties.